Knowledge, attitude and behaviour regarding self-care practices among type 2 diabetes mellitus patients residing in an urban area of South India - Hawal, Nikhil P; S, Shivaswamy M; Kambar, Sanjay; Patil, Shweta; Hiremath, M B (International Multidisciplinary Research Journal, 2013)
Introduction: Diabetes mellitus is a major health problem in India with individual, social and economical consequences. Knowledge, attitude and practice surveys are effective in providing baseline for evaluating intervention programmes. This study was conducted with the aim to know the level of awareness about type 2 diabetes mellitus. Methodology: A cross sectional study conducted to assess the knowledge, attitude and behaviour (KAB) among type 2 diabetes mellitus patients. KAB questionnaire was used to collect data. Results: Out of 1058 patients 992 patients were included for the analysis, rest were excluded due to various reasons. 43.15% were males. Mean age of patients was 55.82 ± 10.2 years. Mean duration of diabetes was 10.2 ± 6.8 years. The mean knowledge score was 4.94, attitude score was 6.29 and behavior score was 1.64. Nearly 38.5% knew definition and types of diabetes. Majority of the participants believed they can control the disease. Dietary modification and exercise among the interviewed subjects was poor. Conclusion: Results revealed good attitude but poor knowledge and practices (behaviour) towards diabetes. We concluded that there is a need for structured programmes to improve attitude and practices of diabetic patients to promote better compliance towards diet, exercise and drug regimen.